Avaliação do potencial remineralizador de géis contendo nano-hidroxiapatita em lesões iniciais de cárie em esmalte - Marques, Vanessa Fontenele (2016)
The formation of enamel’s incipient caries is a reversible process and is regulated by the level of saturation of minerals in the oral fluids. The reversion process takes place through remineralization. The aim of the study was to evaluate, in vitro, the remineralizing potential of experimental gels containing nano-hydroxyapatite, associated or not with fluoride, through a model of induction of enamel’s early caries lesion. For this study, bovine incisors were cut into enamel blocks and randomized in five groups: GC (gel without fluoride and without nano-hydroxyapatite); GF (experimental fluoride gel); GN (nano-hydroxyapatite gel); GNF (nano-hydroxyapatite gel and fluoride); GFC (commercial fluoride gel 1.23%). The specimens were subjected to a cariogenic challenge in order to chemically induce an early caries lesion. The cariogenic challenge was performed through immersing the samples in 2 mL of demineralizing solution/mm2 of exposed enamel for 36h at 37ºC under agitation. Right after this, the gels were applied only once during 4 minutes and the specimens were subjected to a pH-cycling model for 8 days, alternating between 4 hours in demineralizing solution an 20 hours in remineralizing solution. The Knoop microhardness test analysis was initially performed; after inducing caries in enamel; and after pH-cycling. The longitudinal-cut microhardness was executed after the last day of pH-cycling. Right after this, using scanning electron microscopy (SEM), the specimens’ superficial characteristics were evaluated and the chemical compositions of each group were evaluated with Fourier Transform Infrared (FTIR) spectroscopy. The data obtained were subjected to the analysis of variance and then to the T test (p<0,05). There has been no significant statistical difference between the experimental groups (GF, GN, GNF, GFC); however, there have been differences between these and the group GC. As to the longitudinal cut’s microhardness, the data did not show any differences between the groups. The analysis of chemical composition using FTIR showed no differences between the chemical compositions of the samples evaluated. SEM revealed distinct superf icial characteristics between the groups. The gels were efficient in remineralizing enamel’s early caries lesions, but not in depth. The association between nano-hydroxyapatite and fluoride did not bring about any synergetic effects.